Works of Richard Sibbes ; v. 5 - Sibbes, Richard, 1577-1635; Grosart, Alexander B. (Edinburgh, Scotland Banner of truth, 1977)
Contents : v. 5 : Expositions and treatises from portions of several of the Epistles of St Paul
Keywords: Bible. N.T. Epistles of Paul -- commentaries